Neuroinflammation and Neutrophils: Modulation by Ouabain - Leite, Jacqueline Alves; Cavalcante-Silva, Luiz Henrique Agra; Ribeiro, Martina Raissa; de Morais Lima, Geovanni; Scavone, Cristoforo; Rodrigues-Mascarenhas, Sandra (Frontiers in Pharmacology, 2022)
Cardiotonic steroids are natural compounds that present many physiological and pharmacological functions. They bind Na+/K+-ATPase (NKA) modifying cellular ion concentration and triggering cell signaling mechanisms without altering ion balance. These steroids are known to modulate some immune responses, including cytokine production, neutrophil migration, and inflammation (peripherally and in the nervous system). Inflammation can occur in response to homeostasis perturbations and is related to the development of many diseases, including immune-mediated diseases and neurodegenerative disorders. Considering the neutrophils role in the general neuroinflammatory response and that these cells can be modulated by cardiac steroids, this work aims to review the possible regulation of neutrophilic neuroinflammation by cardiac steroid ouabain.